THE GUIDELINES FOR INSTRUCTIONAL DEVELOPMENT OF BUDDHISM SUNDAY SCHOOL - เพ็ญศักดิ์ณุสรณ์ พงษ์ชัย; สินจินดาวงศ์ สิรินธร (Journal of Roi Et Rajabhat University, 2018)
This research was aimed to study the guidelines for instructional development of Buddhism Sunday School, Wat Cholprathan Rangsarit by used a qualitative research. The instrument was used an in-depth interview form as to interview 21 executives and teachers, both monks and general people 15 monks and 6 general people. The research findings indicated that the guidelines on instruction development of Buddhism Sunday School should emphasize on 6 aspects as: 1) Courses: There should be an adult course provided in order to embed and highlight the issues of virtues and morality. 2) Course promotion activities: Filed trips should be created through the collaboration with students’ parents. 3) Instruction management: Instruction plans as well as manuals should be set for teachers at all levels. 4) Instruction media and facilities: More technologies should be applied to help the instruction. 5) Buildings: The school should give precedence to building arrangement for the instruction suitability; and to building adjustment for more modern looks. 6) Student support: Scholarships should be offered to smart students. More various kinds of food should be prepared. And food receipt among students should also be systematically arranged.